Studies on the Rhenium Complexes derived from substituted Thiazole and Imidazole Ligands - Karim, Md Manzurul; Sutradhar, Sudeepta; Hassan, Kamrul (Journal of the Bangladesh Chemical Society, 2012)
Treatment of [Re2(CO)10(MeCN)2] with 2-(methylmercapto)benzothiazole/2-(methylmercapto)benzimidazole in refluxing benzene resulted in the isolation of compounds [Re2(CO)8(µ-η1,η1-(C7H4NS)SCH3] and [Re2(CO)8(µ-η1,η1-(C7H5N2)SCH3] in moderate yield. The compounds have been characterized by IR, 1H NMR, 13C NMR and mass spectral data. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9698 Journal of Bangladesh Chemical Society, Vol. 24(2), 97-105, 2011